Desempenho e características de carcaça de caprinos de diferentes genótipos submetidos a dois sistemas de terminação. - Batista, Ana Catharina dos Santos (2013)
The objective of this study was to evaluate the performance, gross profit margin, quantitative and qualitative characteristics of goats crossbred Boer x Without Dedined Breed (WDB), Anglo-Nubian x WDB and goats WDB kept in two finishing systems. It was 48 non-castrated goats, 16 ½ Boer x ½ WDB, 16 ½ Anglo-Nubian x ½ WDB and 16 WDB, distributed in two finishing systems: confinement and pasture, based feed Caatinga. In each finishing system were kept eight animals per genotype, with average 170 days old and live weight of 16,46 kg. The animal confinement were superior for weight final dry matter intake expressed in g / kg, g/kg0,75 and percentage of body weight, average daily weight gain and assessed trial period. The goats confinement had higher carcass yield, higher fat percentage, conformation and marbling. The goats confinement had higher body fat percentage and those who remained in the Caatinga higher muscle:fat. Significant interaction for average daily weight gain and trial period for termination system and genotype. The Boer crossbred goats had average daily weight gain superior to other genotypes when kept in confinement. The gross profit margin of Boer goats was higher than the crossbred Anglo-Nubian goats and SPRD. The Anglo-Nubian crossbred goats had higher carcass yield followed SPRD animals and crossbred Boer. The goats crossbred Boer showed greater weight and percentage of ribs that crossbred Anglo-Nubian and weight of the upper leg SPRD. The goats crossbred Anglo-Nubian had the highest percentage of bone and lower muscle: bone compared with crossbred Boer, taking the SPRD presented similar results with other genotypes for both variables. Was no significant effect of genotype for carcass conformation and marbling. The Boer crossbred goats showed better conformed carcasses and greater amount of marbling.